Factors Affecting Farmers Perceptions Against Plant Avocado As a Superior Commodity In West Pasaman Regency - Herda Gusvita; Wawan Sumarno; Abdi Pratama (Fakultas Pertanian Universitas Muara Bungo, 2023)
This study aims to analyze the factors that influence farmers' perception of avocado plants as a leading commodity in West Pasaman Regency. This study has been conducted from June 23 to July 23, 2023. The method used in this study is descriptive. The population in this study is avocado plant farmers in Nagari Koto Baru, Luhak Nan Duo District, West Pasaman Regency, totaling 557 people from 4,040 total farmers in Nagari Koto Baru. Sampling in this study was carried out by simple random sampling. The determination of the number of samples used is the same as the number of samples that have been studied by Firhan Yudha in 2022, which is as many as 85 avocado plant farmers. The data analysis used was multiple linear regression using SPSS version 20. The results showed that farming experience, formal education, non-formal education, motivation, availability of information, land area and monthly income both partially and simultaneously had a significant effect on farmers' perceptions of avocado plants in West Pasaman Regency.